Analýza obsahových a grafických chyb kartografických děl - Chalupková, Klára (Vysoké učení technické v Brně. Fakulta stavební, 2016)
Záměrem diplomové práce je analýza chyb a omylů v analogových a digitálních kartografických dílech. První část práce se zabývá chybami a omyly, které se nejčastěji v kartografických dílech dělají. Ve druhé části je samotná analýza vybraných kartografických děl zobrazující Boskovice. Na závěr byla vytvořena prezentace, která obsahuje nejčastější chyby v kartografických dílech. Tato prezentace bude sloužit pro potřeby výuky předmětu Kartografie.

The intention of the diploma thesis is an analysis of errors and oversights of analogue and digital cartographic works. The first part of the thesis deals with errors and oversights which are the most common in cartographic works. The second part of the thesis deals with analysis of chosen cartographic works that display Boskovice. In the end of this thesis was made a presentation and in presentation are the most often errors in cartographic works. This presentation will be used for teaching purposes for subject Cartography.
Analysis of content- and graphical errors of cartographic works
Keywords: chyby a omyly na mapách; Boskovice; map errors and oversights; Boskovice